(untitled) - Bishop, Robert H. (Boca Raton, Fla., 2002)
Mechatronics has evolved into a way of life in engineering practice, and indeed pervades virtually every aspect of the modern world. As the synergistic integration of mechanical, electrical, and computer systems, the successful implementation of mechatronic systems requires the integrated expertise of specialists from each of these areas.
Thiết kế hệ thống cơ điện tử
Keywords: Cơ điện tử,Mechatronics